(untitled) (Research, Society and Development, 2021)
In view of the improvement of construction techniques and technological innovations, civil construction still faces numerous problems. Uncontrolled exploitation of natural resources has caused major environmental impacts, in addition to the generation and accumulation of debris in urban areas. Thus, recycling appears as a sustainable alternative to reduce the accumulation of this waste. As an option, there is the use of Recycled Aggregates, obtained through Construction and Demolition Waste (CDW). In this sense, the present study aimed to analyze the feasibility of using the CDW through its application in the production of recycled coarse aggregates in concrete. For the tests, the coarse aggregate was replaced in the proportions of 0 (reference line), 10, 20, 30, 40, 50 and 100%, with three samples for each line and age. The dosage of the strokes followed the parameters established by the IPT / EPUSP method. The concretes were analyzed for compressive strength at 7, 14 and 28 days and the samples were evaluated for properties in an anhydrous, fresh and hardened state. The data collected in the tests were tabulated and analyzed for the degree of addition and its correlation with the characteristic resistance. The results allowed to conclude that the use of the residue in the form of aggregate for the concrete, in the proportions of 10% and 20%, does not affect the compressive strength, making it a good alternative.